Splenectomy for wandering spleen with pedicle torsion in a 17-year-old: a case report - Guangchao Liu; Yifei Shen; Cheng Jiao; Yao Zhang; Xin Zhang; Qiujing Meng; Wei Liu (Frontiers in Medicine)
BackgroundWandering spleen is a rare disorder characterized by splenic displacement into the abdominal or pelvic cavity, predisposing to torsion and infarction. Congenital factors (long pedicle, lax ligaments) or acquired conditions (splenomegaly) are the usual causes.Case presentationA 17-year-old female presented with 5 days of escalating abdominal pain. Imaging (contrast-enhanced CT and ultrasound) revealed a pelvic spleen with 360° pedicle torsion and partial infarction. After multidisciplinary review, emergency laparotomy was performed and splenectomy was undertaken. Post-operatively, low-molecular-weight heparin followed by aspirin was prescribed to mitigate post-splenectomy thrombocytosis-related thrombosis. The patient was discharged on day 18 without complications and remained well at follow-up.ConclusionEarly recognition, prompt splenectomy, and individualized anticoagulation guided by hematology input are essential to prevent complications in acute splenic torsion.